Management of waste lubricant oil (WLO): WLO-to-energy through gasification process. (18th August 2018) - Li, Haitao; Li, Jinyong; Zhao, Xueling; Zhang, Guiying; Kong, Qingchi
ABSTRACT: Possibility of synthesis gas (syngas) production from waste lubricant oil (WLO) through gasification process has been investigated. The objective of this work is to develop a comprehensive model to simulate WLO gasification using Aspen Plus simulator. The model was based on Gibbs free energy minimization and validated against the published data. Increase in ER results in CO, H2, and CH4 reduction and CO2 enhancement due to partial oxidation of H2 and CO. Since the standard chemical exergy and lower caloric value of H2 is lower than that of CO and both of values are not considerable for CO2, with increasing SFR (steam-to-fuel ratio) from 0.25 to 1.25, EE (exergy efficiency) and GE (gasification efficiency) were decreased.